Plant cell wall homeostasis is mediated by brassinosteroid feedback signaling - Wolf, Sebastian; Greiner, Steffen (Current biology, 2012)
Summary: Brassinosteroid (BR) signaling is required for normal plant growth as shown by the dwarf phenotype of loss-of-function BR biosynthetic or perception mutants. Despite a detailed understanding of the BR signaling network [1-3], it is not clear how exactly BRs control growth. For instance, genetic sector analysis shows that BRs, in contrast to most other growth regulators, act locally, presumably in an autocrine and/or paracrine mode, suggesting that they have some role in feedback regulation [4, 5]. Here, we show that at least one role for BRs in growth control is to ensure pectin-dependent cell wall homeostasis. Pectins are complex block cell wall polymers [6], which can be modified in the wall by the enzyme pectin methylesterase (PME) [7]. Genetic or pharmacological interference with PME activity causes dramatic changes in growth behavior, which are primarily the result of the activation of the BR signaling pathway. We propose that this activation of BR signaling is part of a compensatory response, which protects the plant against the loss of cell wall integrity caused by the imbalance in pectin modification. Thus, feedback signaling from the cell wall is integrated by the BR signaling module to ensure homeostasis of cell wall biosynthesis and remodeling.